Estimating foreign resource needs for economic development : theory, method, and a case study of Colombia - Vanek, Jaroslav (New York : McGraw-Hill, 1967)
This book is on foreign resource needs for economic development
Includes index.
Includes bibliographical references: p. 172-173.
oo 06/09/2018
Loans
Keywords: Saving and investment; Investments, Foreign; Balance of trade